PENGARUH NILAI YAKOBIAN DAN NILAI KATOLIK PADA KARAKTER PESERTA DIDIK SMP SANTO YAKOBUS KELAPA GADING JAKARTA UTARA - Robertus Afrianus Nanga Noo (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2020)
This study aimed to determine the effect of Yakobian values and Catholic values on thecharacter of students. In this study, the researchers chose all nine grade students in the 2019/2020school year with 142 students as respondents. To determine the effect of Yakobian values andCatholic values on the character of students of this study using regression analysis. To test thevalidity of each questionnaire used Product Moment correlation. The data reliability test used theAlpha Cronbach test and tested the normality of data using the Kolmogorov Smirnov test. Theregression linearity in this study used the f test. The results show the relationship of Yakobian valuesinfluencing the character of students the magnitude of the effect is 0.519. Catholic values affect thecharacter of students the magnitude of influence is 0.214. Suggestions from the results of this study,the need for a shared commitment to continue to live the values of the Jacobian and Catholic valuesby considering the needs of students for the development of the times. Based on the data owned, theCatholic values are still low although it reaches, which is low due to the Catholic values because thestudents of St. James Middle School have a variety of beliefs other than Catholic beliefs.